The Uruguay Round and Net Food Importers - Eiteljorge, Uwe (IMF Working Papers; Working Paper ;, 1995)
This paper attempts to assess the incremental external financing requirements occasioned by changes in world food prices, due to implementation of the Uruguay Round Agreement on Agriculture, for a sample of 57 developing countries. Based on estimates of changes in food prices due to the Round obtained in previous studies, and on detailed data on food trade by country and commodity, the present study shows that the increase in net food import costs are likely to be smaller than 4 percent of net food imports over a period of six years for the countries considered, although for some of the larger trading nations the effect may exceed USD 10 million.